The influence of website design, e-service quality, and e-recovery service quality of Lampung ecotourism on visitor satisfaction (Asian Journal of Economics and Business Management, 2022)
The most crucial factor is that tourism managers must be able to adapt to technological advances, which must make it easier for tourists or visitors to access or make transactions if tourists are going to travel to tourist areas. Given how strategic the tourism sector is, it can become a new model and strategy in national economic development, accompanied by digitalizing services to make it easier for consumers or tourists. This study intends to show the Effect of Website Design, E-Service Quality, and E-Recovery Service Quality Ecotourism Lampung on Visitor Satisfaction in Kiluan Bay and Pahawang Island. The research background is because many ecotourism areas are starting to adapt to increasingly rapid technological developments. However, differences do not match this in the design, good electronic services, and services when problems occur in electronic services. This study uses a quantitative research method with a correlational approach. Methods of data collection are done by distributing questionnaires and documentation. There are two research instrument testing methods, namely validity and reliability tests. The data analysis method is the Correlation Test and Multiple Linear Regression Analysis. The results showed a significant effect of Website Design, E-Service Quality, and E-Recovery Service Quality on Visitor Satisfaction, which was 0.245, and the coefficient of determination (R Square) was 0.090. It can be concluded that the Effect of Website Design, E-Service Quality, E-Recovery Service Quality Ecotourism Lampung on Visitor Satisfaction in Kiluan Bay and Pahawang Island is in a Low category.